Lexical Ambiguity in the Podcast Titled "Close the Door" by Deddy Corbuzier on Kompas.com - Oveh Aulia Putri; Farah Zulfa Az-Zahro; Tatu Siti Rohbiah (International Journal of Education and Literature, 2026)
This study aims to analyze lexical ambiguity in the Close the Door podcast, hosted by Deddy Corbuzier. The focus of the study includes identifying the types of lexical ambiguity in the form of polysemy and homonymy, analyzing the meaning of ambiguous words or phrases based on the conversational context, and the influence of ambiguity on listeners' comprehension. This study uses a descriptive qualitative approach with semantic analysis as the theoretical basis. The research data were obtained from conversations in the Close the Door podcast published on Kompas.com. The data collection technique was carried out through listening and note-taking of utterances containing lexical ambiguity. The data were then analyzed by identifying the form of ambiguity, determining its type, and interpreting the meaning based on the context of the utterance. The results show that lexical ambiguity in the podcast appears in the form of polysemy and homonymy, influenced by the use of informal and spontaneous language. This ambiguity can lead to different interpretations for listeners, but the conversational context helps clarify the speaker's intended meaning. This research is expected to contribute to the development of semantic studies, particularly regarding lexical ambiguity in spoken-word digital communication media.